تحليل الكتاب الدراسي في اللغة العربية للصف العاشر على قرار وزير الشؤون الدينية رَقْم ١٨٣ لسنة ٢٠١٩ (لســـانـنــا (LISANUNA): Jurnal Ilmu Bahasa Arab dan Pembelajarannya, 2026)
This study aims to analyze the suitability of the content of grade 10 Arabic textbooks with the provisions stipulated in the Decree of the Minister of Religious Affairs (KMA) No. 183 of 2019. The KMA emphasizes the importance of integration between spiritual, social, knowledge, and skill competencies in teaching materials. The method used in this research is descriptive qualitative with a literature study approach and content analysis of textbooks published by Tiga Serangkai, the latest edition. The research was conducted in the even semester of the 2024/2025 academic year. The results showed that most of the materials in the textbooks were in accordance with the provisions of KMA 183, especially in the spiritual and social aspects. However, there are still shortcomings in some basic competencies (KD) in the realm of knowledge and skills that are not thoroughly accommodated in all types of learning materials such as istima', kalam, qira'ah, kitabah, and qawaid. Therefore, revision or reinforcement through additional teaching strategies is needed by teachers to cover these shortcomings so that learning objectives are achieved optimally. This research is expected to be a reference for teachers and curriculum developers in improving the quality of Arabic teaching materials at the Madrasah Aliyah level.
Keywords: Arabic textbooks, content analysis, madrasah curriculum.